Smart prayer mat: A textile-based pressure sensor to assist elderly with cognitive impairment in praying activity - Ismail, Juhaida; Md Noor, Nor Laila; Wan Mohd Isa, Wan Abdul Rahim (2015)
The older adults will eventually experience unavoidable changes in their cognitive, physical and perceptual ability.Several assistive technologies have been used to support the physical, emotional and social needs of the elderly to enable them to perform their daily activities but lack the support for the activities related to their spiritual needs.We present our work where we explore the intersections of technological development and spiritual practices. As we argue that supporting the praying needs will support the spiritual needs of the older adults, we proposed a technological aid for supporting the praying activity among elderly Muslims as a form of mediated practice.We present the description and design of our Smart Prayer Mat, a smart praying mat embedded with a textile-based sensor that prompts audible cues to alert elderly Muslims with cognitive impairment of the completion of ritual cycles (raka’ahs) while performing their prayer practices.This novel aid will shed new light upon the convergence of technology and spirituality, techno spiritual space.